Problem-Based Learning (PBL) Instructional Materials for Enhancing Mathematics Learning Outcomes of Elementary School Students - Dewi Masyita Faradillah; Putra, Deni Adi; Meirza Nanda Faradita (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
This study aims to 1) describe the application of Problem Based Learning (PBL)-based powerpoint teaching materials which can improve mathematics learning outcomes for elementary students, and2) describe the increase in mathematics learning outcomes after applying learning using Problem BasedLearning power point teaching materials (PBL). This type of research is Classroom Action Research(CAR). The subjects of this research were fifth grade students at MI AL Mustofa Surabaya, totaling 23students consisting of 11 male students and 12 female students. The results showed that 1) the applicationof Problem Based Learning-based power point teaching materials was carried out for two cycles accordingto the stages of the PBL model and 2) power point teaching materials could improve student learningoutcomes, namely in the first cycle the percentage of completeness 69.56% entered good category and incycle II the percentage of completeness 89.95% is in the very good category. Suggestions from this studyare PBL-based power point teaching materials so that they can be applied to other subjects and materials.